Training of Technology-Based Management For Multi-Purpose Cooperative (Koperasi Serba Usaha) Karya Mentulik (KSU-KM), Riau - Astri Ayu Purwati; Muhammad Luthfi Hamzah; Febdwi Suryani (Comment: an International Journal of Community Development, 2019)
Farmer group is a forum for the members to act jointly in agricultural business. In its management, Multi-Purpose Cooperative (Koperasi Serba Usaha) Karya Mentulik (KSU-KM), as a forum accomodating farmer groups in Mentulik, Kab. Kampar, Riau, requires a good management to establish an advanced KSU-KM cooperative that is able to achieve a shared vision and mission. Hence, the community service activity was conducted in KSU-KM Mentulik by involving all 5 Cooperative administrators. In this activity, Information system has been designed in the form of an accounting recording system, SMS Gateway and Cooperative Website. The information system was created with the aim that the technology could help the management in managing cooperative activities and that the existence of KSU-KM could be known by wide communities in order to expand KSU-KM cooperative partners. Training was also given to all KSU-KM administrators to provide the understanding and application of the information system. Through this activity, the evaluation results show that the management had good understanding and benefited from the information system that enable to make the work effective and efficient.